Arten der Gattung Leucopis aus dem nördlichen Kaukasus (Diptera: Chamaemyiidae). - Tanasijtschuk, Vitalij Nikolajevitsch (Contributions to Entomology = Beiträge zur Entomologie, 1961)
The above paper deals with 9 species of the Chamaemyiid genus Leucopis, which were found during summer field work, stationary investigations and two expeditions to the Northern Caucasus District. There is given a key to Leucopis species of this district, based on male genitalia only, descriptions of these species, including 5 new ones, and biological dates. Morphological characters of the larvae of two species are described. Male genitalia are considered as fundamental characters for the identification of the Leucopis species. Nomenclatural Acts auraria Tanasijtschuk & Trjapicyn, 1961 (Leucopis), spec. n. monticola Tanasijtschuk & Trjapicyn, 1961 (Leucopis), spec. n. pallidolineata Tanasijtschuk & Trjapicyn, 1961 (Leucopis), spec. n. pseudomelanopus Tanasijtschuk & Trjapicyn, 1961 (Leucopis), spec. n. caucasica Tanasijtschuk & Trjapicyn, 1961 (Leucopsis), spec. n.